A Study on the Integration of Artificial Intelligence and Music - Keskin, Harun; Keskin, Bilge Türkün (ARTic, 2025)
One of the remarkable developments of the last half century, artificial intelligence has become an inseparable part of daily life, actively used by billions of people, by constantly developing. Artificial intelligence technologies have been used in the music industry for a long time and have brought dynamism to the market in many different areas. The developed models offer innovative approaches such as voice recognition, composing and producing lyrics, production, sound and music synthesis, music personalization, and voice cloning. In this study, general information is given about the use of artificial intelligence, one of today's rapidly developing technologies, in the field of music, and current applications in the sector are examined. In particular, artificial intelligence-supported music production models were emphasized and new compositions were made for the lyrics of the song Adı Zeytin, which won the third prize in a composition competition; elements such as tempo, melodic structure, rhythmic order and prosody were compared with the scores of the composed songs and the song that won the third prize. In addition, examples from current academic studies in national and international literature on the interaction between artificial intelligence and music were given, and the scientific basis of the subject was revealed  Keywords: Music, Artificial intelligence, Music technologies, Music production with artificial intelligence